2003
DOI: 10.1086/377024
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeSnapshot Study of Variable Stars in Globular Clusters: The Inner Region of NGC 6441

Abstract: We present the results of a Hubble Space Telescope snapshot program to survey the inner region of the metal-rich globular cluster NGC 6441 for its variable stars. A total of 57 variable stars were found, including 38 RR Lyrae stars, six Population II Cepheids, and 12 long-period variables. Twenty-four of the RR Lyrae stars and all of the Population II Cepheids were previously undiscovered in ground-based surveys. Of the RR Lyrae stars observed in this survey, 26 are pulsating in the fundamental mode with a mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(163 citation statements)
references
References 73 publications
9
153
1
Order By: Relevance
“…Nemec, Nemec, & Lutz (1994) derived metal-dependent period-luminosity (P L) relations in various optical photometric bands both in the fundamental and in the first overtone modes but subsequently Kubiak & Udalski (2003) found that all the observed T2CEPs in the OGLE II (Optical Gravitational Lensing Experiment; Udalski et al 1992) sample, with periods in the range ∼0.7 to about 10 days, satisfy the same P L relation. This result was then confirmed by Pritzl et al (2003) and Matsunaga et al (2006) for GGCs, by Groenewegen, Udalski, & Bono (2008) for the Galactic Bulge and again by Soszyński et al (2008) on the basis of OGLE III data.…”
Section: Introductionsupporting
confidence: 52%
“…Nemec, Nemec, & Lutz (1994) derived metal-dependent period-luminosity (P L) relations in various optical photometric bands both in the fundamental and in the first overtone modes but subsequently Kubiak & Udalski (2003) found that all the observed T2CEPs in the OGLE II (Optical Gravitational Lensing Experiment; Udalski et al 1992) sample, with periods in the range ∼0.7 to about 10 days, satisfy the same P L relation. This result was then confirmed by Pritzl et al (2003) and Matsunaga et al (2006) for GGCs, by Groenewegen, Udalski, & Bono (2008) for the Galactic Bulge and again by Soszyński et al (2008) on the basis of OGLE III data.…”
Section: Introductionsupporting
confidence: 52%
“…Nevertheless, like Classical Cepheids, these variables can be useful for measuring distances since they too obey a period-luminosity relationship (e.g. McNamara 1995; Pritzl et al 2003;Soszyński et al 2008). …”
Section: Type-ii Cepheidsmentioning
confidence: 99%
“…These are 16 out of the ∼100 GGCs hosting RRLs . To characterize the role played by the metallicity in shaping their pulsation properties they were divided, according to their metal content (Harris 1996) -including 60RRab, 1RRd and 41RRc belonging to the two metal-rich globulars (Pritzl et al 2001(Pritzl et al , 2002(Pritzl et al , 2003 . From left to right UBVRI light curves of the RRab variable V100.…”
Section: Comparison With Rrls In Globulars and In Dwarf Galaxiesmentioning
confidence: 99%